Port performance factors and their interactions: A systems thinking approach - Yos Sunitiyoso; Shimaditya Nuraeni; Noorhan Firdaus Pambudi; Tutik Inayati; Ilham Fadhil Nurdayat; Fikri Hadiansyah; Adhya Rare Tiara (Asian Journal of Shipping and Logistics (AJSL), 2022)
Indonesia's inter-island movement of goods relies heavily on sea transportation because it can transport large volumes of goods at a reasonable cost. However, it is challenging to meet the same pricing standards everywhere, particularly for regions located far from the production centres. The government initiated the Motorways of the Sea Program to tackle this issue. Stakeholders in Indonesia's maritime logistics should be involved in the implementation processes, including the port operators, the shipping industry, and the government as a regulator and infrastructure enabler. However, the democratic, decentralised, and pluralistic nature of Indonesia's government, culture, and bureaucracy has challenged the implementation of the Motorways of the Sea Program. Based on a systematic map of each stakeholder's interests, barriers, and expectations, the study used a systems thinking approach to capture the interactions among stakeholders' activities and policies in the maritime logistics system. A causal loop diagram and a stock and flow diagram were developed to provide a holistic view of the system. Several systemic forces that became the leverages of the system's performance were identified. The most important factors are infrastructure development, both physical and non-physical infrastructures that include information and communication technology, service procedures, and human capital supporting the service system.
Keywords: 650; Causal loop diagram; Maritime logistics; Motorways of the sea program; Stock and flow diagram; Systems thinking approach